Humanitarianism and the Sendai Framework: A 10-Year Review of Converging and Diverging Paths - Rodrigo Mena (International Journal of Disaster Risk Science)
Abstract Humanitarian action and disaster risk reduction are essential in addressing global vulnerability to disasters and crises. The Sendai Framework for Disaster Risk Reduction 2015–2030 (SFDRR), adopted in 2015, has garnered significant attention for its role in fostering disaster risk reduction. The role the SFDRR plays vis-à-vis humanitarian action represents a crucial space where policies, practices, and priorities (could) converge and diverge. Understanding the dynamics of this SFDRR-humanitarian action relationship is essential for advancing both disaster risk reduction and humanitarian goals. This article comprehensively examines this relationship since the adoption of the SFDRR. Employing a multimethod approach, including a systematic literature review, mapping exercise, and expert interviews, the study identified key themes and challenges in integrating the SFDRR within humanitarian action. Findings indicate that while SFDRR references are prevalent in post-disaster discussions, their full integration into humanitarian strategies remains nascent. Notably, advancements in anticipatory humanitarian action represent primary arenas for SFDRR integration within humanitarianism. The role of the International Disaster Response Law in bridging SFDRR and humanitarianism also emerged as an important finding. The study also underscored blurred distinctions between humanitarianism and disaster-related actions, highlighting the limited systemic integration of the SFDRR by traditional humanitarian actors. Moving forward, the study advocates for improved collaboration between humanitarian and disaster management sectors to strengthen disaster prevention, response, and mitigation. By examining the relationship between SFDRR objectives and modern humanitarian practices, this research aims to enhance disaster preparedness, response, and recovery strategies, alongside other crisis management approaches.